Dispersão de sementes pelo mico-leão-preto, Leontopithecus chrysopygus (Primates, Callitrichidae) em um fragmento de Mata Atlântica - Alcolea, Mirela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Primates can be efficient seed dispersers, having an important role on the regeneration of degraded areas and forest fragments. The aim of the study was to determine the role of the black lion tamarin (Leontopithecus chrysopygus) as a seed disperser through: 1) the characterization of the fruits consumed by the black-lion-tamarin and the identification of those that are dispersed; 2) the analysis of the spatial distribution of seeds dispersed and their dispersal distances; 3) the determination of the effect of gut passage on seed germination. We followed one group of black lion tamarins for 22 days in a fragment of Tropical Semideciduous Forest from March to September of 2015. We collected group behavior data, mapped the fruit trees they fed on and the locations of the feces, and collected the fruits consumed and the fecal samples. To determine the effect of gut passage on germination success, we compared the percentage of germination of defecated seeds, seeds with pulp, and without pulp. The black lion tamarins spent 25.6% of the time feeding, 85% of these feeding events being on fruits. They dispersed ten from the 11 species they consumed to a mean distance of 343.8 ± 225.8 m, within a home range of 82.9 ha. The spatial distribution of seeds dispersed was associated to the location of the feeding trees as well to the resting and sleeping trees. The passage of seeds through the black lion tamarins' gut significantly increased the germination success of 3 out of 9 tested species and had a neutral effect on the others. Although the study occurred during the dry season, a period of low fruit availability, fruits constituted a large part of the black lion tamarin's diet. In addition, the black lion tamarins dispersed the seeds of almost all of the species consumed within a large area and at long distances, which indicates that the species can be considered as an effective seed disperser...

Primatas podem ser eficientes dispersores de sementes, exercendo importante papel na regeneração de áreas degradadas e fragmentos florestais. O estudo teve como objetivo caracterizar o papel do mico-leão-preto (Leontopithecus chrysopygus) na dispersão de sementes, buscando: 1) determinar as características dos frutos consumidos pelo mico-leão-preto e quais são de fato dispersos por ele; 2) analisar a distribuição espacial das sementes dispersas, assim como as distâncias de dispersão; e 3) avaliar o efeito da passagem pelo trato digestório sobre a germinação das sementes. Um grupo de micos-leões-pretos foi acompanhado durante 22 dias (aprox.190 horas de observação), em um fragmento de Floresta Estacional Semidecídua de março a setembro de 2015. Foram coletados dados de comportamento do grupo, localização das árvores de alimentação por frutos e das fezes, coleta de frutos consumidos e coleta das fezes. Para determinar o efeito da passagem no trato digestório na germinação das sementes, comparamos o sucesso de germinação entre sementes defecadas, sementes com polpa e sementes sem polpa. Os micos-leões-pretos passaram 25,6% do tempo se alimentando, sendo que, 85% desses eventos de alimentação foram por frutos. Eles dispersaram 10 das 11 espécies consumidas, pela distância média de 343,8 ± 225,8 m, em uma área de vida de 82,9 ha. A distribuição espacial das sementes era associada à localização das árvores de alimentação e dos dormitórios e árvores de descanso. A passagem pelo tubo digestório dos micos aumentou significativamente o sucesso de germinação de 3 das 9 espécies testadas e teve um efeito neutro nas outras espécies. Mesmo em um período de menor disponibilidade de frutos, o mico-leão-preto apresentou grande consumo de 5 frutos, dos quais mostrou capacidade de dispersar quase todas as espécies consumidas, em uma área extensa e por grandes...
Keywords: Sementes - Disseminação; Primatas; Micos-leões; Florestas; Fragmentos florestais; Lion tamarins